EMPLOYERS’ ROLE IN THE IMPROVEMENT OF SAFETY LEVEL IN ESTONIAN ENTERPRISES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The key persons in safety activities at enterprises are: top manager, his(her) representatives, working environment specialist, all acting for the employer; and working environment representatives, selected by the workers and holding the workers’ rights in safety and health area. The main possibilities to improve the safety level in the firm have the working environment specialists, as they are usually educated and supported by the employer and the law. The current paper is looking for the possibilities to raise the employers’ interest for improvement of their knowledge in safety and through this also the safety level in the workplace. Safety level in 12 Estonian enterprises was investigated using MISHA method (based on standard OHSAS 18001). Some of the firms have implemented OHSAS 18001 or belong to the foreign companies. The investigated enterprises were from different industries and agriculture firms. The safety level is very much depended on the owner of the firm. The larger the enterprise is the better are the possibilities to educate the employers and employees. One of the ideas to improve the safety level at enterprise is the method “learning through the interviews”. The interview is worked out basing on MISHA method. The latter is a tool of quantitative study. The safety performance key elements were divided into three parts: formal, real, combined ones. Three hypothesis were formulated and the area in which they are proved concerning employer’s activities were as follows: H1) Standard OHSAS 18001 has an impact on Formal safety performance in companies (p value< 0.013) – if OHSAS 18001 has been implemented, then: the assignment of tasks and responsibilities in OHS is committed to the top management, the employer is revising the safety policy, and the personnel’s responsibilities in OHS are clearly defined. H2) Standard OHSAS 18001 has an impact on Real safety performance. (p< 0.013) - if OHSAS 18001 is implemented, then: the top manager promotes dissemination of safety policy: the policy is made available to all of the personnel; resources for improvement are arranged by the top management; the top manager arranges meetings in OHS; there is a system for redesigning the workplaces for the persons who have difficulties in coping with the work. H3) Standard OHSAS 18001 has an impact on Combined safety performance (p< 0.007) - if OHSAS 18001 implemented, then: the top management is participating in the preparation of safety policy, top manager is reviewing the safety policy, is it operating effectively? He is informing the external bodies about the company’s safety policy’s effectiveness; the top manager arranges safety training for all of the personnel; there is a plan for reduction of accidents; it has been elaborated by the top manager; the company has a system for measuring the social climate in the company.